THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF WORKLOAD AND COMPETENCE ON EMPLOYEE PERFORMANCE AT PT PLN (PERSERO) UP2B NTB - Putu Yudiadi Pranata; Trianasari; Komang Krisna Heryanda (RADJA PUBLIKA, 2026)
The purpose of this study was to analyze the effect of workload and competence on employee performance with job satisfaction as a mediating variable at PT PLN (Persero) UP2B NTB. The research method used was quantitative with a census approach, involving the entire employee population of 54 people. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the help of SmartPLS software . The results of the study showed that: (1) workload did not have a significant effect on employee performance; (2) competence had a positive and significant effect on employee performance; (3) workload did not have a significant effect on job satisfaction; (4) competence had a positive and significant effect on job satisfaction; (5) job satisfaction had a positive and significant effect on employee performance; (6) job satisfaction did not mediate the relationship between workload and employee performance; (7) job satisfaction partially mediated the relationship between competence and employee performance. The R-square value for job satisfaction was 72.5% and employee performance was 84.1%, with a Goodness of Fit value of 0.770 (high category).